2006
DOI: 10.1107/s1600536806009573
|View full text |Cite
|
Sign up to set email alerts
|

(E)-4-(Isonicotinoylhydrazono)pentanoic acid monohydrate

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (C-C) = 0.004 Å R factor = 0.080 wR factor = 0.185 Data-to-parameter ratio = 13.9For details of how these key indicators were automatically derived from the article, seeThe title compound, C 11 H 13 N 3 O 3 ÁH 2 O, was synthesized by the reaction of acetopropanoic acid and isonicotinoylhydrazide in ethanol. A three-dimensional network of intermolecular O-HÁ Á ÁO, O-HÁ Á ÁN and N-HÁ Á ÁO hydrogen bonds stabilizes the crystal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Recently, a few crystal structures containing the isonicotinohydrazone unit have been reported (Ali et al, 2005;Chen et al, 2006;Guo et al, 2006;Li et al, 2006;Liu & Zhang 2005. Tai et al, 2003and Wardell et al, 2006 and our research group has also reported a crystal structure related to the title compound (Wang & Tang 2006). We have synthesized the title compound by the reaction of 4-pyridylaldehyde and isonicotinoylhydrazide in the presence of ethanol and determined its crystal structure to further expand our research and investigate its antimycobacterial activity.…”
Section: Commentmentioning
confidence: 87%
“…Recently, a few crystal structures containing the isonicotinohydrazone unit have been reported (Ali et al, 2005;Chen et al, 2006;Guo et al, 2006;Li et al, 2006;Liu & Zhang 2005. Tai et al, 2003and Wardell et al, 2006 and our research group has also reported a crystal structure related to the title compound (Wang & Tang 2006). We have synthesized the title compound by the reaction of 4-pyridylaldehyde and isonicotinoylhydrazide in the presence of ethanol and determined its crystal structure to further expand our research and investigate its antimycobacterial activity.…”
Section: Commentmentioning
confidence: 87%
“…Rings of the molecule are twisted away from the hydrazone plane [26]. Geometric properties of substituted-benzaldehyde isonicotinoyl-hydrazone are similar to that of 4-cyanobenzaldehyde isonicotinoyl-hydrazone monohydrate [33][34][35]. In the present subject parameters of 4-cyanobenzaldehyde isonicotinoyl-hydrazone monohydrate bonds (lengths and angles) optimized by HF, B3LYP methods with 6-31++G(d,p) as the basis set are listed in Table 1.…”
Section: Geometrical Structurementioning
confidence: 98%
“…Since the experimental and theoretical bond lengths are not directly compared. However, the title compounds (I and II) of theoretical bond lengths are compared with similar molecules (3,25,26). The bond lengths N11À ÀC12 and N11À ÀC16 of the title compounds (I and II) have been generally found to be 1.320-1.322 and 1.338-1.442 Å using HF and B3LYP with 6-31+G(d,p) basis set.…”
Section: Geometrical Structurementioning
confidence: 99%